Treatment of developmental defect of upper lip with carbon dioxide laser radiation (CO2): First surgical time - Niccoli-Filho, Walter [UNESP]; Murilo-Santos, Lucio [UNESP]; Schubert, Mark; Morosolli, Aline Cantarelli [UNESP] (Taylor & Francis, 2005)
With the exception of the cleft lip, developmental defects (DD) of the lip are rare. The upper lip originates from the ectomesenchyme and is formed by the merging of the nasal medial and lateral processes with the maxillary process. Disturbances during this formation period can cause DD with functional and/or esthetic repercussions. We present a case of DD of the upper lip in a patient with a history of progressive growth of the left lateral portion of the upper lip that occurred from the time of birth until the age of 22 years. Clinical examination revealed hypertrophy of the area from the left philtral columns to the left commissure of the lip, extending the portion of the surface mucosa creating a flaccid and asymptomatic tissue mass. All other buccal structures appeared to be within normal limits and without any evidence of defects or deformities. In the surgical planning we decided to carry out corrective surgery in two phases. The first phase accomplished a conservative excision of the total abnormal labial tissue mass with a CO2 laser radiation (5 W in continuous mode, bunch diameter φ = 0.6 mm with a power density of 768 W/cm2 and fluency of 0.231 J/cm2) being careful to preserve the vermilion portion of the lip. Postsurgical clinical evaluations were done every three days until the skin sutures were removed and then every seven days until two months post surgery. While the entire mass of excessive tissue could not be completely removed, the removal of the excessive mucosal tissue produced a very good outcome relative to lip function, with a good esthetic result without scarring, and good tissue mobility. The results showed that the CO2 laser is an extremely useful instrument that can provide excellent control of the surgical field and allow for healing that produces excellent functional and esthetic results. © 2005 Taylor & Francis.
Keywords: Carbon dioxide laser; Developmental defects; Lip surgery; antibiotic agent; cephalosporin; diclofenac; adult; anamnesis; birth; carbon dioxide laser; case report; clinical examination; clinical feature; esthetics; human; hypertrophy; laboratory test; lip malformation; lip reconstruction; low level laser therapy; male; mouth mucosa; postoperative period; priority journal; scar formation; suture removal; treatment outcome; upper lip; Adult; Carbon Dioxide; Humans; Hypertrophy; Lasers; Lip; Male